Morphology and molecular characteristics of entomopathogenic nematode train S-DL13, Steinernema siamkayai isolated from Vietnam - Trang, Nguyen Nhu; Chau, Nguyen Ngoc (Academia Journal of Biology, 2015)
As first record for Vietnam, a strain of entomopathogenic nematodes, S-DL13 belonging to Steinernema siamkayai has been isolated from coffea soils in Dak Lak province. In general, the morphology of S-DL13 strain is characterized in male by number and arrangement of the genital papillae with 11 pairs of papillae and 1 single papilla, of which 6 precloacal subventral pairs, one precloacal lateral pair, one postclocal subventral pair, one precloacal subdorsal pair and two subterminal subventral pairs; the single preanal papilla is located ventrally between level of precloacal pairs 5 and 6, counded from anterior. Spicule length is 77 ± 5 (65-85) µm in 1st generation and 61 ± 7 (52-69) µm in 2nd generation. Vulva lips protruding prominently, prominent double-flapped epiptygma present. Body length of infective juveniles are smaller than 600 µm as typical for the "carpocapsae" species group. Lateral field with 6 ridges or 7 incisures. Although strain S-DL13 shared many common morphological features with the original description of Steinernema siamkayai, the Vietnamese strain shows some differences such as a slightly shorter body length of infective juveniles (average 426 µm vs 446 µm) and higher index E% (98 vs 96%). Body lengths of 1st and 2nd generation (females) are greater than in the original description (5051μm vs 3937 µm in 1st generation and 2453 vs 1836 µm in 2nd generation); body width has also greater (242 vs 198 µm in 1st generation and 132 μm vs 105 µm in 2nd generation). In addition, the molecular characteristics of the Vietnamese strain, S-DL13 based on ITS rDNA genes provide evidence on the similarity with Thailand strain both in position and genetic length, also located in the same phylogenic clade with the bootrap value as 98 on the ML tree that enable conclussion on the strain S-DL13 belongs to species Steinernema siamkayai.